Dampak Standar Kecantikan terhadap Kognisi Sosial Mahasiswa: Studi Kasus terhadap Teman Sebaya yang Menyimpang di kalangan Mahasiswa/i UINSU - Ainul Mardiyah; Adinda Nurfadillah Azmi; Muhammad Natsir Husein Hrp (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study aims to analyze how socially constructed beauty standards shaped by media, popular culture, and the surrounding environment affect the social cognition of university students in evaluating peers who deviate from mainstream beauty norms. Within the campus environment, students often bring visual biases and prejudices toward others based solely on physical appearance, such as skin tone, body shape, and fashion style. This study adopts a qualitative approach with a case study method. Data were collected through in-depth interviews with four students from the State Islamic University of North Sumatra (UINSU) with diverse backgrounds.The results show that most students initially form judgments based on social schemas influenced by social media, past experiences, and peer environments. However, some participants demonstrated a shift in perspective after engaging in personal reflection, studying social psychology, and experiencing more diverse social interactions. They began to exhibit more empathetic attitudes and fairer judgments. This study highlights the importance of higher education in fostering critical awareness and promoting inclusive values and social sensitivity within academic environments.